2023
DOI: 10.1021/acs.inorgchem.3c01303
|View full text |Cite
|
Sign up to set email alerts
|

Stronger Together! Mechanistic Investigation into Synergistic Effects during Homogeneous Carbon Dioxide Hydrogenation Using a Heterobimetallic Catalyst

Abstract: A series of group 6 heterobimetallic complexes [M0;IrIII] (M = Cr, Mo, W) were synthesized and fully characterized, and the catalytic behavior was studied. The heterobimetallic complex [Mo0;IrIII] (C1) was by far the most active and has shown a considerable synergistic effect, with both metals actively participating in homogeneous carbon dioxide hydrogenation, leading to formate salts. Based on theoretical calculations, the synergistic interaction is due to Pauli repulsion, lowering the transition state and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 70 publications
0
0
0
Order By: Relevance
“…27 Lately, Hawkins and co-workers reported the heterobimetallic Mo/Ir-catalyzed hydrogenation of CO 2 to formate with a TON of 128. 28 In 2020, computational studies by Liu and Ke 29 on group VI NHC-supported complexes revealed that these low electronegativity and low oxidation state complexes could be effective catalysts for CO 2 hydrogenation. Prompted by this study, we delve into the CO 2 hydrogenation using Mo catalysts bearing bidentate phosphine ligands with varied bite angles.…”
Section: Introductionmentioning
confidence: 99%
“…27 Lately, Hawkins and co-workers reported the heterobimetallic Mo/Ir-catalyzed hydrogenation of CO 2 to formate with a TON of 128. 28 In 2020, computational studies by Liu and Ke 29 on group VI NHC-supported complexes revealed that these low electronegativity and low oxidation state complexes could be effective catalysts for CO 2 hydrogenation. Prompted by this study, we delve into the CO 2 hydrogenation using Mo catalysts bearing bidentate phosphine ligands with varied bite angles.…”
Section: Introductionmentioning
confidence: 99%
“…Although several examples of synergism in catalysis by such mixed-metal clusters were discovered, the widespread application of such catalysts was hampered by their instability, resulting in the formation of several catalytically active fragments [5]. The application of catalysts in which the two different metal ions were bridged by heterodifunctional ligands proved more successful [6][7][8][9], especially with early/late heterobimetallic complexes [10]. It was recognized from the beginning of such studies that in bimetallic dinuclear complexes, the two metal ions may not only cooperate in the catalysis of a given reaction but also act independently, allowing consecutive catalytic transformations.…”
Section: Introductionmentioning
confidence: 99%